2000
DOI: 10.1016/s0014-5793(00)01150-9
|View full text |Cite
|
Sign up to set email alerts
|

Rap1‐suppressed tumorigenesis is concomitant with the interference in Ras effector signaling

Abstract: Expression of Rap1 blocks epithelial growth factorinduced extracellular signal-regulated kinases (ERKs) activation. However, recent studies demonstrated that Rap1 mediates ERKs activation induced by nerve growth factor. The anti-oncogenic effect of Rap1 has been reported but its mechanism remains unclear. To evaluate the correlation between the anti-transforming effect and the activation of ERKs, we transfected rap1 cDNA into Hep3B cells and selected stable transfectants. The Rap1 transfectants completely lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Moreover, in nude mice xenograft assays, Rap1 suppresses their intrinsic tumorigenic capacity [ 59 ]. Rap1 also acts as a suppressor of tumorigenesis by inhibiting TPA-(phorbol ester) or insulin-induced Ras/Raf/MEK/ERK activation and cell proliferation in Hep3B cells [ 60 ]. In contrast, experiments developed in other human liver cancer cell lines (HepG2, HepG2.2.15 and SMMC-7721) support the involvement of Rap1 in hepatitis B virus (HBV)-related HCC pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in nude mice xenograft assays, Rap1 suppresses their intrinsic tumorigenic capacity [ 59 ]. Rap1 also acts as a suppressor of tumorigenesis by inhibiting TPA-(phorbol ester) or insulin-induced Ras/Raf/MEK/ERK activation and cell proliferation in Hep3B cells [ 60 ]. In contrast, experiments developed in other human liver cancer cell lines (HepG2, HepG2.2.15 and SMMC-7721) support the involvement of Rap1 in hepatitis B virus (HBV)-related HCC pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no much information about Rap function in HCC, and that available is quite controversial [ 32 ]. Rap1 could suppress tumorigenesis in Hep3B cells [ 52 ] or contribute to HCC induction [ 53 ]. More recent studies reported an upregulation of either Rap2B or Rap1B [ 54 , 55 ] expression in HCC, associated with increased proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…The first data were obtained from different human cancer databases and indicate that RAPGEF1 mRNA levels increase in samples from HCC patients and in patient-derived xenografts, as compared to non-pathological liver samples [23] . Later, new analyses of cancer databases revealed that RAPGEF1 mRNA levels gradually increase in HCC patients as the disease progresses (from stages I to III), being also higher in HCC cell lines as compared to adult hepatocytes [46] [Table 1]. This increase in C3G levels is associated with a lower survival [46] , as is the presence of somatic mutations and other genetic alterations in RAPGEF1 gene (amplification, deletion, etc.)…”
Section: C3g and Other Ras Gefs In Liver Cancermentioning
confidence: 99%